MEASUREMENT OF SOIL REACTION FORCES BY A SINGLE FLAT WHEEL ON THE SLOPE SOIL BIN - Irwin Syahri CEBRO; Ramayanty BULAN; Agustami SITORUS (My University, 2022)
The ability of a cage wheel to climb slopes depends on the grip of the lug on the sloped soil. A lug wheel that sinks deeper will generate more force when climbing. This study aimed to measure the soil reaction force on a single flat lug wheel in the slope soil bin so that the optimal lug angle is obtained to enhance the ability of cage wheels to climb sloped soil. The experiment was carried out using a model of a single flat lug wheel (length of 10 cm, width of 3.5 cm, radius of 30.4 cm, and slope of 30o). Measurements of soil reaction forces on the lug were carried out on five lug angles (-15o, 0o, 15o, 30o, 45o) at three various sinkage depths (2.5 cm, 5 cm, 7.5 cm) at a rotational speed of 11 rpm. The moisture content, density, porosity used in this study were 45.61% (d.b.), 1.02 (g/cm), 44.02%. In addition, the particle size distribution of sand, clay, and silt are 8.038%, 13.396%, and 78.564%, respectively. The limits of soil consistency used in this study, including the plastic limit, water limit, and index limit, were 64.57%, 80.86%, and 16.29%, respectively. A set of measurement and data logger equipment is used to measure the reaction forces of the soil. The results showed that at the angles of -15 and 0 the lugs were able to penetrate the soil faster and deeper to produce a greater pulling force. This implies that a smaller angle of inclination will be more beneficial to the tractors wheel applied for climbing than a greater angle of inclination.
Keywords: Atterberg limits; Angle of repose; Silt; Soil Mechanics and Vehicle Dynamics